Innovative Aspect of E-Commerce Development in Ukraine - Gamova, Iryna; Shportiuk, Nataliia; Duginets, Ganna; Busarieva, Tatiana (Dr. Viktor Koval, 2024)
Introduction. The share of e-trading in the total volume of the Ukrainian retail sales market tends to increase. Since innovative trade approaches open new perspectives and provide the possibility of doing business in conditions of significant challenges, the role of e-commerce in restoring the country's economy becomes more significant. The social role of e-commerce as a source of vital goods for a population is also growing. Therefore, the study of the e-commerce market and analysis of the impact of war on its development have become important tasks. Aim and tasks. The purpose of this study is to examine the state of the e-commerce market using statistical data, analyze the impact of the war on the development of e-commerce, identify the main market trends, and forecast the main indicators of e-commerce. This determines the following tasks: establishing the peculiarities of the e-commerce market in Ukraine, establishing obstacles to the development of e-commerce, identifying opportunities that e-trading opens up for Ukrainian entrepreneurs, and determining the conditions to be taken into account in the transition of retail trade to e-trading under the challenges of war.. Results. The negative impact of significant market changes in the 2022-2023 was compensated by the growth in active e-commerce users. A change in the growth rate of users by 40% in 2022 was confirmed. This indicates that hostilities changed the range of e-commerce products and that the market share of basic necessities exceeded 50%. The highest annual revenue per user for food products will be 89.4% ahead of the product group closest to this indicator. According to the indicator “Average income from e-commerce per client”, it is predicted to reach 2019 only in 2026. Sales changes for the main product groups in 2024 have been established. According to the “Highest annual revenue per user” indicator, food products will exceed the value for 2023 by 25% and personal care products by 9.4%. Conclusions. Innovative technologies (e-marketplace, analysis of buyer profiles, omnichannel communication with consumers, m-trading, etc.) that contribute to the development of e-commerce and the interaction of these technologies and market needs are identified. The peculiarities of the Ukrainian e-commerce market during the war were established. Obstacles to the development of e-commerce and the opportunities that e-trading opens for Ukrainian entrepreneurs have been identified. The conditions that must be considered during the transition from retail trade to e-trading due to the challenges of war, which is especially important for small and medium-sized enterprises, are determined.